Sistem Informasi Manajemen Surat pada Dinas Pendapatan, Pengelolaan Keuangan dan Aset Daerah Kabupaten Pati - Hayu Andarwati; R. Rizal Isnanto; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2014)
Abstract - Documents handling at Dinas Pendapatan, Pengelolaan Keuangan dan Aset Daerah Kabupaten Pati was done manually and was not computerized. Because of that, it is needed to build documents management information system to automate the document control activity at department include the function of documents recording, documents making, and documents tracking. For gaining the purpose, a research must be done. That research used Framework for Application System Thinking (FAST) with eight phase, that is scope definition, problem analyst, requirement analyst, logical design, decision analyst, physical design and integration, construction and testing, and also installation and delivery. This research was implemented by using PHP, HTML, and Javascript as programming language and MySQL as database. System testing was done by using black box testing method.The result from this research is documents management information system.